A case of invasive aspergillosis in CGD patient successfully treated with Amphotericin B and INF-γ - Gerami-Shoar Mohsen; Saadat Farshid; Zomorodian Kamiar; Mamishi Setareh; Tarazooie Bita; Siadati Seyad Ahmad (BMC, 2005)
Abstract Background Chronic granulomatous disease (CGD) is a rare disorder of phagocytes in which absence of superoxide and hydrogen peroxide production in phagocytes predisposes patients to bacterial and fungal infections. The most common fungal infections in these patients are caused by Aspergillus species. Case presentation Here, we describe Aspergillus osteomyelitis of the ribs and hepatic abscess in a 5-year-old boy. The patient was successfully treated with Amphotericin B and INF-γ. Conclusion With respect to the high frequency of aspergillosis in the CGD patient, immune deficiency should be investigated in patients with invasive aspergillosis. Moreover, using antifungal drugs as prophylaxis can improve the quality of life in these patients.